1981
DOI: 10.3109/00016358109162287
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and caries

Abstract: On the basis of existing literature, efficient oral hygiene was found to have a caries preventive effect. The quality of the cleaning appears to be more important than the frequency of its performance. Professional tooth cleaning at regular intervals may inhibit caries on all tooth surfaces. The effect of self-performed oral hygiene has been demonstrated mainly on free smooth surfaces and on front teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 40 publications
3
66
0
11
Order By: Relevance
“…There is no strong evidence of a clear relationship between oral cleanliness and levels of dental caries 192 . The Health Education Authority in England concluded that 'although caries cannot develop without the presence of plaque, plaque removal by tooth brushing cannot in itself be advocated for caries prevention.…”
Section: Promotion Of Good Oral Hygienementioning
confidence: 99%
“…There is no strong evidence of a clear relationship between oral cleanliness and levels of dental caries 192 . The Health Education Authority in England concluded that 'although caries cannot develop without the presence of plaque, plaque removal by tooth brushing cannot in itself be advocated for caries prevention.…”
Section: Promotion Of Good Oral Hygienementioning
confidence: 99%
“…But the relationship between toothbrushing and oral cleanliness on the one hand and dental caries on the other is equivocal 132 . Bellini, Arneberg and von der Fehr 132 concluded that toothbrushing habits had a questionable effect on caries.…”
Section: Oral Cleanliness and Dental Cariesmentioning
confidence: 99%
“…By contrast, fluoridated dentifrices reduce caries only in subjects that maintain effective oral hygiene (2,11,38). A significant relationship between caries experience and oral hygiene has been apparent in the United States and western Europe since 1980 (3,6), a generation following the introduction of fluoridated dentifrices in 1965 (40). Adults who are older and grew up using nonfluoridated dentifrices showed no association of caries experience with oral hygiene.…”
mentioning
confidence: 98%